Overall feasibility assessment of polyester polyurethane concrete used as steel bridge deck pavement - Niu, Shi-Lei; Wang, Jun-Yi; Wang, Zuo-Cai; Wang, Dong-Hui; Sun, Xiao-Tong; Zhao, Xi (Frontiers in Materials, 2022)
Traditional pavement materials used in the orthotropic steel bridge deck suffer from various pavement distresses and thus reduce the service life of the steel bridge. Therefore, this study proposed a novel engineered material named polyester polyurethane concrete (PPUC) for the steel bridge deck pavement. Indoor laboratory experiments and numerical comparison analysis were conducted to comprehensively assess the feasibility of PPUC as the steel bridge deck pavement and ordinary Portland cement (OPC), guss asphalt concrete (GAC), asphalt mastic concrete (SMAC) and epoxy asphalt concrete (EAC) were used as references compared with PPUC. After the specimens of PPUC were prepared by mixing polyester polyurethane binder (PPUB) and aggregate with the binder-aggregate ratio of 15%, the specimens were subjected to compressive test, splitting tensile test, flexural tensile strength test, wheel tracking test, low-temperature cracking test, freeze-thaw splitting test, shear test and pull-out test. The mechanical performance comparison of different pavement structures with different materials was also analyzed using finite element analysis method. Results show that PPUC presents higher mechanical properties (compressive, tensile and flexural strength) compared to OPC, and it has good durability properties compared to SMAC, GAC and EAC, such as high temperature stability, low temperature cracking resistance and water stability. In addition, PPUC has strong adhesive property with steel deck and does not change significantly with temperature changes. The mechanical performance comparison results indicate that PPUC pavement structure can improve the overall stiffness of the steel bridge deck and protect the wear layer. These results support that the PPUC has a promising application for the steel bridge deck pavement.